Joan Rivers : a piece of work [videorecording (DVD)] - Stern, Ricki; Rivers, Joan; Rivers, Melissa, 1969-; Rickles, Don; Diller, Phyllis; Griffin, Kathy, 1960- (IFC Films, 2010)
The cameras follow trailblazing comic, Joan Rivers, for a year and cover her entire career from her break on the Carson show, to her heartbreak over the suicide of her husband, and her role on Celebrity Apprentice. Rivers reveals her relentless desire to keep working with humor and empathy. Wickedly funny and surprisingly moving, Rivers is once again returned to the spotlight she so richly deserves and cements her reputation as one of stand-up's towering figures.